Kathmandu Dilemma: Resetting India-Nepal Ties : A Book Review - Prasain, Indira Devi (Medha: A Multidisciplinary Journal, 2025)
The aim of the study is to analysis of Ranjit Rae’s Kathmandu Dilemma: Resetting India-Nepal Ties (2021), which provides a comprehensive analysis of the complex relationship between India and Nepal, examining political, economic, and social dynamics. This is a qualitative study, employing secondary data without engaging primary data. The book addresses key issues such as the Maoist insurgency, the peace process, border disputes, the impact of the 2015 earthquake, and Nepal’s growing ties with China. Through ten chapters based on the author’s diplomatic experience and qualitative methods, Rae explores the evolving bilateral relationship, focusing on Nepal’s constitutional developments, economic challenges, and strategic positioning. While offering valuable insights from an Indian perspective, the book highlights the complexities of cross-border relations, including historical tensions and cultural connections. Although the analysis predominantly reflects India’s viewpoint, the work remains an essential contribution to understanding the current state of India-Nepal relations and provides recommendations for strengthening future cooperation.